(Cu1/3Nb2/3)4+ ionic substituting effects, low-temperature sintering behaviors, and improved temperature stability of Ba3Nb4Ti4O21 microwave dielectric ceramics. Issue 9 (1st May 2022) - Chen, Yawei; Zhang, Meirong; Yang, Hongyu; Li, Enzhu
Abstract: In this study, (Cu1/3 Nb2/3 ) 4+ complex cation and BaO–ZnO–B2 O3 glass frit were adopted to solve the high sintering temperature and poor temperature stability of Ba3 Nb4 Ti4 O21 ceramics. It is shown that pure Ba3 Nb4 Ti4 O21 phase was formed when Ti site was partially replaced by (Cu1/3 Nb2/3 ) 4+ cation. The increasing number of dopants decreases the dielectric polarizability, correspondingly, the dielectric constant and temperature coefficient of the resonance frequency values are reduced consistently. The variation of the Q × f value is determined by internal ionic packing fraction and external sintering densification. The (Cu1/3 Nb2/3 ) 4+ cation effectively decreases the suitable sintering temperature from 1200 to 1050 °C while greatly improving the temperature stability. BaO–ZnO–B2 O3 glass was used to further improve the low-temperature sintering characteristics of Ba3 Nb4 Ti4 O21 ceramics. It is proven that the addition of glass frits effectively decreases the temperature to 925 °C with combinational excellent microwave dielectric properties: εr ∼55.6, Q × f ∼5700 GHz, τf ∼3 ppm/ ° C, making the Ba3 Nb4 Ti4 O21 ceramics promising in the applications of low-temperature cofired ceramic technology.